Hubungan kepuasan komunikasi dengan komitmen pekerja Jabatan Khidmat Pengurusan Majlis Perbandaran Johor Bahru Tengah (MPJBT) - Johar, Nurulazian (2017)
The study is about the relationship of communication satisfaction with employee commitment. It aims to identify the level of employee’s commitment to the organization, identify the level of employee’s communication satisfactio to the organization, the relationship between communication satisfaction factors with commitment and also identify factors that most influence employee’s commitment. This study is quantitative study and uses instruments of Communication Satisfaction Questionnaire (CSQ) by Down and Hazen (1977) which was distributed to 89 respondents in the Jabatan Khidmat Pengurusan Majlis Perbandaran Johor Bahru Tengah. This study used a mean score analysis, correlation analysis and multiple regression analysis. The results show the level of commitment of respondents to the organization is moderate, while the level of communication satisfaction factors are high for all four factors which are media quality factor, the climate communication, communication among employees and individual feedback. The analysis also showed that the four factors studied communication satisfaction has a positive relationship with the employees' commitment to the organization and overall analysis of the study found that the communication among employees is the most dominant factor in influencing employee commitment. In conclusion, these studies generally show that the commitment of employees in the organization is influenced by four factors study. Accordingly, this study suggests the organization to take proactive steps in addressing the issue of organizational communication. In addition, the organization also need to create a positive communication environment and a commitment so that any problems regarding communication and commitment in oganization can be prevent in the future.